Association of cholesterol levels with hemorrhagic transformation and cerebral edema after reperfusion therapies. (March 2023) - Escudero-Martínez, Irene; Thorén, Magnus; Matusevicius, Marius; Cooray, Charith; Zini, Andrea; Roffe, Christine; Toni, Danilo; Tsivgoulis, Georgios; Ringleb, Peter; Wahlgren, Nils; Ahmed, Niaz
Background: The association between cholesterol levels and cerebral edema (CED) or hemorrhagic transformation (HT) as an expressions of blood-brain barrier (BBB) dysfunction after ischemic stroke is not well established. The aim of this study is to determine the association of total cholesterol (TC) levels with the incidence of HT and CED after reperfusion therapies. Methods: We analyzed SITS Thrombolysis and Thrombectomy Registry data from January 2011 to December 2017. We identified patients with data on TC levels at baseline. TC values were categorized in three groups (reference group ⩾200 mg/dl). The two primary outcomes were any parenchymal hemorrhage (PH) and moderate to severe CED on follow up imaging. Secondary outcomes included death and functional independence (mRS 0–2) at 3 months. Multivariable logistic regression analysis adjusted for baseline factors including statin pretreatment was used to assess the association between TC levels and outcomes. Results: Of 35, 314 patients with available information on TC levels at baseline, 3372 (9.5%) presented with TC levels ⩽130 mg/dl, 8203 (23.2%) with TC 130–200 mg/dl and 23, 739 (67.3%) with TC ⩾ 200 mg/dl. In the adjusted analyses, TC level as continuous variable was inversely associated with moderate to severe CED (OR 0.99, 95% CI 0.99–1.00, p = 0.025) and as categorical variable lower TC levels were associated with a higher risk of moderate to severe CED (aOR 1.24, 95% CI 1.10–1.40, p = 0.003). TC levels were not associated with any PH, functional independence, and mortality at 3 months. Conclusions: Our findings indicate an independent association between low levels of TC and higher odds of moderate/severe CED. Further studies are needed to confirm these findings.